ROS-independent ER stress-mediated NRF2 activation promotes warburg effect to maintain stemness-associated properties of cancer-initiating cells - Chang, Ching-Wen; Chen, Yu-Syuan; Tsay, Yeou-Guang; Han, Chia-Li; Chen, Yu-Ju; Yang, Cheng-Chieh; Hung, Kai-Feng; Lin, Chao-Hsiung; Huang, Tsung-Yen; Kao, Shou-Yen; Lee, Te-Chang; Lo, Jeng-Fan (Cell death & disease, 2018)
Cancer-initiating cells (CICs) are responsible for tumor initiation, progression, and therapeutic resistance; moreover, redox homeostasis is important in regulating cancer stemness. Previously, we have identified that cancer cells containing low intracellular reactive oxygen species levels (ROS Low cells) display enhanced features of CICs. However, the specific metabolic signatures of CICs remain unclear and are required for further characterization by systemic screenings. Herein, we first showed CICs mainly relying on glycolysis that was important for the maintenance of stemness properties. Next, we revealed that NRF2, a master regulator of antioxidants, was able to maintain low intracellular ROS levels of CICs, even though in the absence of oxidative stress. We further characterized that NRF2 activation was required for the maintenance of CICs properties. Of ROS Low cells, NRF2 activation not only directly activates the transcription of genes encoding glycolytic enzymes but also inhibited the conversion of pyruvate to acetyl-CoA by directly activating pyruvate dehydrogenase kinase 1 (PDK1) to lead to inhibition of tricarboxylic acid (TCA) cycle; therefore, to promote Warburg effect. A positive regulatory ROS-independent ER stress pathway (GRP78/p-PERK/NRF2 signaling) was identified to mediate the metabolic shift (Warburg effect) and stemness of CICs. Lastly, co-expression of p-PERK and p-NRF2 was significantly associated with the clinical outcome. Our data show that NRF2 acting as a central node in the maintenance of low ROS levels and stemness associated properties of the CICs, which is significantly associated with the clinical outcome, but independent from ROS stress. Future treatments by inhibiting NRF2 activation may exhibit great potential in targeting CICs.